Subfailure Overstretch Induces Persistent Changes in the Passive Mechanical Response of Cerebral Arteries - Bell, E. David; Sullivan, Jacob W.; Monson, Kenneth L. (Frontiers in Bioengineering and Biotechnology, 2015)
Cerebral blood vessels are critical in maintaining the health of the brain, but their function can be disrupted by traumatic brain injury (TBI). Even in cases without hemorrhage, vessels are deformed with the surrounding brain tissue. This subfailure deformation could result in altered mechanical behavior. This study investigates the effect of overstretch on the passive behavior of isolated middle cerebral arteries (MCAs), with the hypothesis that axial stretch beyond the in vivo length alters this response. Twenty nine MCA sections from eleven ewes were tested. Vessels were subjected to a baseline test consisting of an axial stretch from a buckled state to 1.05*in vivo stretch (λIV) while pressurized at 13.3 kPa. Specimens were then subjected to a target level of axial overstretch between 1.05*λIV (λz=1.15) and 1.52*λIV (λZ=1.63). Following overstretch, baseline tests were repeated immediately and then every 10 minutes, for 60 minutes, to investigate viscoelastic recovery. Injury was defined as an unrecoverable change in the passive mechanical response following overstretch. Finally, pressurized MCAs were pulled axially to failure. Post-overstretch response exhibited softening such that stress values at a given level of stretch were lower after injury. The observed softening also generally resulted in increased nonlinearity of the stress-stretch curve, with toe region slope decreasing and large deformation slope increasing. There was no detectable change in reference configuration or failure values. As hypothesized, the magnitude of these alterations increased with overstretch severity, but only once overstretch exceeded 1.2*λIV (p<0.001). These changes were persistent over 60 minutes. These changes may have significant implications in repeated TBI events and in increased susceptibility to stroke post-TBI.